hepatitis B and C and syphilis vulnerability related infections among institucionalized disadvantaged youth in São Paulo, Brazil - Carvalho, Herúclito B.; Seibel, Sérgio D.; Burattini, Marcelo N.; Massad, Eduardo; Reingold, Arthur (Brazilian Journal of Sexually Transmitted Diseases, 2003)
[...]